Pelvic Organ Prolapse - Najmutdinova D. K.; Gadoyeva D. A. (Researchparks Publishing, 2022)
In recent years, more and more attention has been paid to the issues of prolapse of the genital organs. This is largely due to increase in women's life expectancy and the need to provide them with a decent quality of life, since quite often; prolapse is accompanied by dysfunction of the pelvic organs. In the literature of recent years, there are many the body of information relating to this problem. However, most of these researches considers therapeutic or vertebral neurological problems, while the widespread. This pathology causes the need for additional studies, which will make it possible to determine the choice of subsequent treatment.